Application of a superparametric finite shell element to the calculation of turbine blade vibrations - Bogomolov, S. I.; Lutsenko, S. S.; Nazarenko, S. A. (Kluwer Academic / Plenum Publishers Corporation, 1982)
Determination of the natural frequencies and forms of vibrations of turbine blades with the present level of knowledge is one of the chief problems that have to be solved at the design stage of turbines in order to ensure vibration reliability. Greater possibilities of devising more correct mathematical models of blades and universal methods of investigating their vibrations are opened up in connection with the application of the finite element method.

Для расчета колебаний лопаток турбомашин сложной геометрии используют суперпараметрические оболочечные конечные элементы.
Keywords: superparametric finite element; shell; calculation; turbine; blade; математическая модель; метод конечных элементов; лопатки турбомашин